Prevalence and causes of low vision among urban and rural school children - Verma, Ritesh; Rathi, Manisha; Dhull, C. S.; Sachdeva, Sumit; Phogat, Jitender (International Journal Of Community Medicine And Public Health, 2018)
Background: The objective of this study is to determine the prevalence and the causes of low vision among school going children in and around Rohtak district of Haryana, India. Such information is important in planning for prevention of low vision and blindness strategies. Methods: 2028 school children studying in class 1-5 were screened in the school premises. Visual acuity was assessed with Snellen’s chart and colour vision was tested with ishihara colour vision book. Those with vision <6/18 in both eyes were assessed at our tertiary care hospital to determine the cause of low vision. Results: A total of 2028 children were enrolled in our study. 58 children were found to have uncorrected visual acuity less than 6/18 (functional low vision) in the better eye. Uncorrected refractive error was the most common cause of functional low vision (51.72%) among the 2028 children enrolled in our study followed by amblyopia (32.7%), cataract (5.1%), corneal opacity (5.1%), retinal dystrophy (5.1%), nystagmus (1.7%) and optic nerve glioma (1.7%). Conclusions: The overall prevalence of low vision in our study is higher as compared to previous studies. A comparison between academic performances of children with low vision and rest of the children showed that children with low vision tend to perform poor academically. The prevalence of amblyopia was significantly higher in children from the rural background which emphasizes the importance of rural school screening programmes. It was found that amblyopia was significantly higher in females as compared to males in both rural and urban areas.